Effect of micro-electrolytic fillers on the oil removal efficiency in wastewater. Issue 2 (April 2019) - Guan, Di; Liu, Yu; Zheng, Guochen; Zheng, Jixin
Abstract: Aims to degrease the oily wastewater, the micro-electrolysis treatment with modified fillers was applied in this paper. The effect of micro-electrolytic filler on the oil removal was studied to determine the optimum proportion of carbon-iron, and corresponding preparation conditions. The result shows a relatively greater oil removal rate as 81.4% with safe effluent quality.